2023
DOI: 10.3389/fmicb.2022.1081035
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus ubiquitin-conjugating enzyme pI215L inhibits IFN-I signaling pathway through STAT2 degradation

Abstract: African swine fever virus (ASFV) is the causative agent of one of the most lethal diseases affecting domestic pig and wild boar, which is endangering the swine industry due to its rapid expansion. ASFV has developed different mechanisms to evade the host immune response, including inhibition of type I IFN (IFN-I) production and signaling, since IFN-I is a key element in the cellular antiviral response. Here, we report a novel mechanism of evasion of the IFN-I signaling pathway carried out by the ASFV ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…The further analysis unveiled that the interaction of MGF300-4L with IKK β results in the autophagic degradation of IKK β . The immune regulatory protein of ASFV degrades key molecules involved in the IFNs and NF- κ B signaling pathway via the autophagy pathway, a commonly employed immunoevasion mechanism by ASFV [ 44 ]. For example, the virulence-associated factor A137R protein of ASFV can inhibit the production of IFNs by mediating the autophagy-induced lysosomal degradation of TBK1 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The further analysis unveiled that the interaction of MGF300-4L with IKK β results in the autophagic degradation of IKK β . The immune regulatory protein of ASFV degrades key molecules involved in the IFNs and NF- κ B signaling pathway via the autophagy pathway, a commonly employed immunoevasion mechanism by ASFV [ 44 ]. For example, the virulence-associated factor A137R protein of ASFV can inhibit the production of IFNs by mediating the autophagy-induced lysosomal degradation of TBK1 [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibody anti-tubulin (B-5-1-2) (T-5168) was purchased by Sigma, Kanagawa, Japan. Polyclonal antibody anti-I125L was previously generated in our lab [24]. Monoclonal antibody anti-p32(S-5C1) was previously generated [34].…”
Section: Antibodies For In Vitro Experimentsmentioning
confidence: 99%
“…The type I IFN-induced JAK/STAT pathway has also been described as being controlled by ASFV [20], further relating type I IFN to virulence. Some of the viral factors that control this pathway during ASFV infection [21][22][23][24][25] have also been identified. The identification and study of these factors are fundamental for the development of live attenuated vaccines (LAVs), which are currently the most realistic strategy for developing a vaccine against ASFV.…”
Section: Introductionmentioning
confidence: 99%
“…ASFV pI215L (UBCv1) can interact with IRF9 and mediate the degradation of IRF9 via autophagy-lysosome pathway, which is independent of its ubiquitin-conjugating enzyme activity [ 85 ]. Additionally, ASFV pI215L (UBCv1) can also mediate the degradation of STAT2 via ubiquitin-proteasome pathway, which is dependent on its ubiquitin-conjugating enzyme activity [ 86 ]. In addition, Zhang et al identified pMGF360-9L as also working as an inhibitor of JAK/STAT pathway [ 87 ].…”
Section: Suppression Of Ifn-i Production and Ifn-induced Antiviral Re...mentioning
confidence: 99%